ANALISIS TATANIAGA TELUR AYAM RAS (STUDI KASUS PT CAHAYA MARIO BROTHER GROUP) (Jurnal Ekonomi Bisnis dan Akuntansi, 2022)
The objectives of this study are (1) Analyzing the channels and functions of purebred chicken egg trading (2) Analyzing tataniaga margins, farmer's share and the ratio of profits and costs of purebred chicken egg trading (3) Analyzing the cost efficiency of purebred chicken egg trading at PT. Light Mario Brother's Group Sidrap, Mario Village, Kulo District, Sidrap Regency. This research was conducted at PT. Light Mario Brother Group Sidrap, Mario Village, Kulo District, Sidrap Regency. The data used in this study are primary data and skunder. There are three institutions in the purebred chicken egg trading system at PT. Light Mario Brother's Group Sidrap, a manufacturer/breeder, wholesaler and retailer. Each commercial institution performs different administrative functions. There are three channels formed in the egg trading system, namely commerce channel 1 (producer - consumer); Commerce channel 2 (manufacturer - merchant, retailer - consumer); and Commerce channel 3 ( producer - wholesaler - retailer - consumer). Producers should distribute purebred chicken egg commodities efficiently and need to cooperate or partner with parties who are willing to accommodate producer products (end consumers) at high and relatively stable prices